Comparing the immunomodulatory properties of bone marrow, adipose tissue, and birth-associated tissue mesenchymal stromal cells - Mattar, Philipp; Bieback, Karen (Frontiers in immunology, 2015)
Mesenchymal stromal cells (MSC) have gained immense attraction in regenerative medicine, tissue engineering and immunotherapy. This is based on their differentiation potential and the supply of pro-regenerative and immunomodulatory signals. MSC can be isolated from a multitude of tissue sources, but mainly bone marrow, adipose tissue and birth-associated tissues (e.g. umbilical cord, cord blood, placenta) appear to be relevant for clinical translation in immune-mediated disorders. However, only a few studies directly compared the immunomodulatory potency of MSC from different tissue sources. This review compiles the current literature regarding the similarities and differences between these three sources for MSCs with a special focus on their immunomodulatory effects on T-lymphocyte subsets and monocytes, macrophages and dendritic cells.